2008
DOI: 10.1037/0096-3445.137.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Positive transfer and negative transfer/antilearning of problem-solving skills.

Abstract: The present study examined how self-regulatory processes influenced problem solving behavior under conditions in which people were either re-exposed to their prior learning, or experienced someone else's. In a series of four experiments, participants solved two complex control tasks that were identical in structure but varied in presentation format. Participants either learnt to solve the second task, based on their original learning phase from the first task, or learnt to solve the second task based on anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 115 publications
(360 reference statements)
4
44
0
3
Order By: Relevance
“…What are the conditions that enable and support such learning? Generally, it has been argued that the lack of evidence for causal learning found in previous studies results from methodological rather than psychological factors [18]. This argument also receives empirical support.…”
Section: Conditions Promoting Causal Learning During Control Taskssupporting
confidence: 53%
See 1 more Smart Citation
“…What are the conditions that enable and support such learning? Generally, it has been argued that the lack of evidence for causal learning found in previous studies results from methodological rather than psychological factors [18]. This argument also receives empirical support.…”
Section: Conditions Promoting Causal Learning During Control Taskssupporting
confidence: 53%
“…(1b). than psychological factors may explain the dissociation [18], and many have reported findings in which there is a close correspondence between structural knowledge and control performance [18,19]. For example, by regularly probing knowledge of structural relations during learning, people show insight into the relations that govern the behavior of the system.…”
Section: Goals and Hypothesesmentioning
confidence: 99%
“…Second, consistent with previous studies (Osman 2008a(Osman , 2008b, there was no advantage of active-based learning over observation-based learning in both measures of performance. Third, also consistent with previous studies (Burns & Vollmeyer, 2002;Osman 2008aOsman , 2008bSanderson, 1989), the present study revealed an association between the accuracy of participants' knowledge of the structure of the system they were controlling, and their ability to control it. Fourth, posttest questions indicated that when identifying the learning trials they experienced during the learning phase from two others, participants were more accurate in conditions in which the learning phase generated instance and rule-based knowledge compared with instance only conditions.…”
Section: Discussionsupporting
confidence: 78%
“…The fi ndings from this study converge with previous evidence suggesting that instructions designed to encourage hypothesis testing and other similar meta-cognitive processes (e.g., monitoring-tracking one's online goal-directed behaviors) do not interfere with the uptake of skilled knowledge, as some have claimed, but instead enhance skilled performance (Berardi-Coletta et al, 1995;Osman, 2008aOsman, , 2008b. Thus, the present study shows that hypothesis testing, rather than the active engagement with a procedural task, is necessary for the successful uptake of knowledge and its application to mastering a complex control system.…”
Section: Why Were Associations Found Between Declarative and Procedursupporting
confidence: 79%
See 1 more Smart Citation